IINS Vs CALLY Index: A Battle of Prognostic Value in NSCLC Patients Following Surgery - Cheng H; Ma J; Zhao F; Liu Y; Wu J; Wu T; Li H; Zhang B; Liu H; Fu J; He H; Zhu C; et al. (Journal of Inflammation Research)
Hao Cheng,1,* Jiao Ma,1,* Fengyu Zhao,2 Yiwei Liu,3 Jie Wu,4 Tao Wu,1 Hui Li,1 Boxiang Zhang,3 Hui Liu,5 Junke Fu,3 Haiqi He,3 Cailin Zhu,3 Hong Ren,3 Chengcheng Yang,2 Sida Qin3 1Department of Rehabilitation, The First Affiliated Hospital of Xi’an Jiaotong University, Xi’an, Shaanxi, People’s Republic of China; 2Department of Oncology, The First Affiliated Hospital of Xi’an Jiaotong University, Xi’an, Shaanxi, People’s Republic of China; 3Department of Thoracic Surgery, The First Affiliated Hospital of Xi’an Jiaotong University, Xi’an, Shaanxi, People’s Republic of China; 4Department of Radiation Oncology, Shaanxi Provincial People’s Hospital, Xi’an, Shaanxi, People’s Republic of China; 5Biobank, The First Affiliated Hospital of Xi’an Jiaotong University, Xi’an, Shaanxi, People’s Republic of China*These authors contributed equally to this workCorrespondence: Sida Qin, Department of Thoracic Surgery, The First Affiliated Hospital of Xi’an Jiaotong University, 277 West Yanta Road, Xi’an, Shaanxi, 710061, People’s Republic of China, Tel +86 15388666585, Email qinsida@xjtu.edu.cn Chengcheng Yang, Department of Oncology, The First Affiliated Hospital of Xi’an Jiaotong University, 277 West Yanta Road, Xi’an, Shaanxi, 710061, People’s Republic of China, Tel +86 17629260656, Email ccyang@xjtufh.edu.cnObjective: This research sought to assess the predictive potential of the inflammation-immunity-nutrition score (IINS) and the high-sensitivity C-reactive protein-albumin-lymphocyte (CALLY) index in individuals with NSCLC post-surgery.Methods: The study enrolled 506 patients with NSCLC undergoing R0 resection at the First Affiliated Hospital of Xi’an Jiaotong University. The training cohort was analyzed utilizing X-tile software to identify the ideal threshold values for categorizing high-sensitivity C-reactive protein, albumin, lymphocyte count, and the CALLY index. The predictive significance of the IINS and CALLY index was evaluated through Kaplan–Meier survival curves and univariate and multivariate Cox regression analyses. Predictive capabilities of the IINS and CALLY index were compared utilizing receiver operating characteristic (ROC) curve analysis, time-dependent ROC curve analysis, and decision curve analysis (DCA). Internal validation was performed in the validation cohort and all data from both the training and validation cohorts using Kaplan–Meier curves and DCA.Results: Patients with lower IINS exhibited prolonged overall survival (OS), whereas those with lower CALLY had shorter OS. Multivariate analysis identified N stage, NSE, and IINS as independent prognostic factors for individuals with NSCLC. ROC analysis revealed that IINS provided superior prognostic performance to CALLY and other traditional indicators (CAR, PLR, and NLR). Time-dependent ROC analyses and DCA further confirmed the superior prognostic value of IINS over the CALLY index at 1, 2, and 3 years.Conclusion: This study reveals that both the IINS and CALLY index are effective in forecasting the prognosis of individuals with NSCLC following surgery, with the IINS demonstrating superior prognostic efficacy to the CALLY index.Keywords: NSCLC, prognosis, IINS, CALLY index